Evaluación de dos técnicas ecológicas (trampas) para control de barrenador del hueso del aguacatero (Heilipus spp), en la comunidad de Pueblo Nuevo, parroquia Monte Olivo, provincia del Carchi - Carapaz Bolaños, Fredy Gustavo (2018)
SUMMARY Although Heilipus spp (avocado bone borer) is a pest that has a negative impact on productivity, there is a lack of scientific and basic information on the control and management of the avocado pest. taking into account the above, the research was carried out with the aim of improving the performance of avocado cultivation in the community of Pueblo Nuevo, province of Carchi, in the first instance the plague Heilipus spp (avocado bone borer) was identified, in several crops in the area using the trapping method to take the appropriate measures, then the population of the pest was reduced using 2 cultural methods friendly to the ambient, in the first method, blue colored plastic placed in a zig-zag uniformly distributed throughout the crop was used, and in the second method a plastic wrap around the trunk of the avocado trees was used in 10% of the population of study, it was possible to verify and visualize that the insect climbs the tree mainly walking on the trunk, since the plastic wrapping method was the most effective in trapping more insects, it is necessary to continue investigating this insect because it affects the visual presentation of the fruit which decreases the commercialization, likewise improving the most efficient method observed to make it more effective when controlling the plague, Integrated pest management (IPM) not only helps improve the productivity of a crop but also decreases the cost of production and what is more, we take care of the environment.